2018
DOI: 10.1016/j.buildenv.2017.12.019
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variation of window opening behaviors in two naturally ventilated hospital wards

Abstract: A B S T R A C TNatural ventilation enables personal control, and occupant behaviors in window opening play a decisive role on natural ventilation performance, indoor air quality (IAQ), and/or airborne infection risk in a hospital setting. The occupant behaviors differ significantly from different building types with different functions and living habits. Based on a one-year field measurement in two general hospital wards in Nanjing, China, the effects of air quality (i.e. indoor CO 2 concentration and outdoor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(26 citation statements)
references
References 38 publications
1
25
0
Order By: Relevance
“…However, it should be noted that no significant literature was found about motorized windows surrounding human-building interactions. As evidenced in the following sections, the majority of existing studies were focused on office buildings and few studies were found about the identification of key variables influencing window control behavior in residential [46]- [49] educational [50], and healthcare [51] buildings.…”
Section: Operable Windowsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it should be noted that no significant literature was found about motorized windows surrounding human-building interactions. As evidenced in the following sections, the majority of existing studies were focused on office buildings and few studies were found about the identification of key variables influencing window control behavior in residential [46]- [49] educational [50], and healthcare [51] buildings.…”
Section: Operable Windowsmentioning
confidence: 99%
“…Personal control of windows differs significantly between different building typologies [51] and climate type [52], according to function, usability and living habits. Patterns of interaction between the occupants and windows vary according to building end-use and, in particular, between office and residential buildings.…”
Section: Rq1: What Influences Behavior?mentioning
confidence: 99%
“…This study was designed to improve the understanding of the interactions among indoor and outdoor environmental parameters and the roles they play in influencing people's WOB. Many quantitative methods have been used to model WOB such as logistic regression [5,16,18,19,28,29], Markov chains [30], Gauss distribution [30], and deep learning [31]. No studies have been found to apply SEM in the WOB field.…”
Section: Discussionmentioning
confidence: 99%
“…Logistic regression remains a popular method among researchers for modeling WOB [5,16,18,19,28,29]. However, other modeling approaches have also been used in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…Yun et al [28] have used this method and developed a model predicting window behavior of occupants in an office building in the UK. Using data collected from two hospital wards in Nanjing in China, Shi et al [29] have developed a logistic window behavior model, and got a prediction accuracy of 70%.…”
Section: Introductionmentioning
confidence: 99%